A Comparison Between Digital Radiography, Computed Tomography, and Magnetic Resonance in the Detection of Gunshot Residues in Burnt Tissues and Bone. Issue 3 (22nd October 2013) - Amadasi, Alberto; Borgonovo, Simone; Brandone, Alberto; Di Giancamillo, Mauro; Cattaneo, Cristina
Abstract The radiological search for GSR is crucial in burnt material although it has been rarely tested. In this study, thirty‐one bovine ribs were shot at near‐contact range and burnt to calcination in an oven simulating a real combustion. Computed tomography (CT) and magnetic resonance (MR) were performed before and after carbonization and compared with former analyses with DR (digital radiography); thus comparing the assistance, the radiological methods can provide in the search for GSR in fresh and burnt bone. DR demonstrated the greatest ability in the detection of metallic residues, CT showed lower abilities, while MR showed a high sensitivity only in soft tissues. Thus, DR can be considered as the most sensitive method in the detection of GSR in charred bones, whereas CT and MR demonstrated much less reliability. Nonetheless, the MR ameliorates the analysis of gunshot wounds in other types of remains with large quantities of soft tissues.